RELIGIOUS MODERATION AND ITS CHALLENGES IN INDONESIAN EDUCATION: CASE STUDY AT MTSN 1 TRENGGALEK - Fauzi, Diky Mohamad (Dinamika Penelitian: Media Komunikasi Penelitian Sosial Keagamaan, 2023)
This article examines religious moderation in Indonesia, with a focus on students at Madrasah Tsanawiyah Negeri (MTsN) 1 Trenggalek. The study utilizes surveys and data analysis using Power BI. Survey results indicate a high level of religious moderation and tolerance among students. They acquire religious knowledge from various sources, including religious leaders, religious teachers, Quranic teachers (guru/ustadz mengaji), and social media. However, there is a shift in the trend of sources for religious preaching information, with social media platforms like TikTok becoming the primary source. The article also discusses the role of kiai and challenges in maintaining religious moderation in the digital age.